Bone Morphogenetic Protein 9 Protects against Neonatal Hyperoxia-Induced Impairment of Alveolarization and Pulmonary Inflammation - Chen, Xueyu; Orriols, Mar; Walther, Frans J.; Laghmani, El Houari; Hoogeboom, Annemarie M.; Hogen-Esch, Anne C. B.; Hiemstra, Pieter S.; Folkerts, Gert; Goumans, Marie-José T. H.; ten Dijke, Peter; Morrell, Nicholas W.; Wagenaar, Gerry T. M. (Frontiers in Physiology, 2017)
Aim: Effective treatment of premature infants with bronchopulmonary dysplasia (BPD) is lacking. We hypothesize that bone morphogenetic protein 9 (BMP9), a ligand of the TGF-β family that binds to the activin receptor-like kinase 1 (ALK1)-BMP receptor type 2 (BMPR2) receptor complex, may be a novel therapeutic option for BPD. Therefore, we investigated the cardiopulmonary effects of BMP9 in neonatal Wistar rats with hyperoxia-induced BPD. Methods: Directly after birth Wistar rat pups were exposed to 100% oxygen for 10 days. From day 2 rat pups received BMP9 (2.5 µg/kg, twice a day) or 0.9% NaCl by subcutaneous injection. Beneficial effects of BMP9 on aberrant alveolar development, lung inflammation and fibrosis, and right ventricular hypertrophy (RVH) were investigated by morphometric analysis and cytokine production. In addition, differential mRNA expression of BMP9 and its receptor complex: ALK1, BMPR2 and Endoglin, and of the ALK1 downstream target transmembrane protein 100 (TMEM100) were studied during the development of experimental BPD. Expression of the BMP9 receptor complex and TMEM100 was studied in human endothelial and epithelial cell cultures and the effect of BMP9 on inflammatory cytokine production and TMEM100 expression was studied in endothelial cell cultures. Results: ALK1, ALK2, BMPRII, TMEM100 and Endoglin were differentially expressed in experimental BPD, suggesting a role for BMP9-dependent signalling in the development of (experimental) BPD. TMEM100 was expressed in the wall of blood vessels, showing an elastin-like expression pattern in arterioles. Expression of TMEM100 mRNA and protein was decreased after exposure to hyperoxia. BMP9 treatment of rat pups with hyperoxia-induced experimental BPD reduced alveolar enlargement, lung septal thickness and fibrosis, and prevented inflammation, but did not attenuate vascular remodelling and RVH. The anti-inflammatory effect of BMP9 was confirmed in vitro. Highest expression of ALK1, BMPR2 and TMEM100 was observed in human endothelial cell cultures. Stimulation of human endothelial cell cultures with BMP9 reduced their pro-inflammatory cytokine response and induced TMEM100 expression in pulmonary arterial endothelial cells. Conclusion: BMP9 protects against neonatal hyperoxia-induced BPD by improving aberrant alveolar development, inflammation and fibrosis, demonstrating its therapeutic potential for premature infants with severe BPD.